An Agrarian History of the Mwenezi District, Zimbabwe, 1980-2004 - Manganga, Kudakwashe (University of the Western Cape, 2013)
Magister Philosophiae (Land and Agrarian Studies) - MPhil(LAS) === The thesis examines continuity and change in the agrarian history of the Mwenezi District, southern Zimbabwe since 1980. It analyses agrarian reforms, agrarian practices and development initiatives in the district and situates them in the localised livelihood strategies of different people within the Dinhe Communa Area and the Mangondi resettlement Area in Lieu of the Fast-Track Land Reform Programme (FTLRP) since 2000. The thesis also examines the livelihood opportunities and challenges presented by the FTLRP to the inhabitants of Mwenezi.The thesis contributes to the growing body of empirical studies on the impact of Zimbabwe's ongoing land reform programme and to debates and discourses on agrarian reform. === South Africa